RASSF1A independence and early galectin‐1 upregulation in PIK3CA‐induced hepatocarcinogenesis: new therapeutic venues. Issue 5 (20th November 2021) - Scheiter, Alexander; Evert, Katja; Reibenspies, Lucas; Cigliano, Antonio; Annweiler, Katharina; Müller, Karolina; Pöhmerer, Laura‐Maria‐Giovanna; Xu, Hongwei; Cui, Guofei; Itzel, Timo; Materna‐Reichelt, Silvia; Coluccio, Andrea; et al.
Abstract : Aberrant activation of the phosphoinositide 3‐kinase (PI3K)/AKT/mTOR and Ras/mitogen‐activated protein kinase (MAPK) pathways is a hallmark of hepatocarcinogenesis. In a subset of hepatocellular carcinomas (HCCs), PI3K/AKT/mTOR signaling dysregulation depends on phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase, catalytic subunit alpha (PIK3CA) mutations, while RAS/MAPK activation is partly attributed to promoter methylation of the tumor suppressor Ras association domain‐containing protein 1 (RASSF1A). To evaluate a possible cocarcinogenic effect of PIK3CA activation and RASSF1A knockout, plasmids expressing oncogenic forms of PIK3CA (E545K or H1047R mutants) were delivered to the liver of RASSF1A knockout and wild‐type mice by hydrodynamic tail vein injection combined with sleeping beauty‐mediated somatic integration. Transfection of either PIK3CA E545K or H1047R mutants sufficed to induce HCCs in mice irrespective of RASSF1A mutational background. The related tumors displayed a lipogenic phenotype with upregulation of fatty acid synthase and stearoyl‐CoA desaturase‐1 (SCD1). Galectin‐1, which was commonly upregulated in preneoplastic lesions and tumors, emerged as a regulator of SCD1. Co‐inhibitory treatment with PIK3CA inhibitors and the galectin‐1 inhibitor OTX008 resulted in synergistic cytotoxicity in human HCC cell lines, suggesting novel therapeutic venues. Abstract : Hydrodynamic tail vein injection of phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase, catalytic subunit alpha (PIK3CA) mutant forms E545K and H1047R induces stepwise hepatocarcinogenesis in mice, independent of Ras association domain‐containing protein 1 status. Gene expression analyses revealed an early increase in galectin‐1, which regulates the lipogenic enzyme stearoyl‐CoA desaturase‐1. PIK3CA‐ and galectin‐1 inhibitors act synergistically, pointing at novel therapeutic strategies.